Labor supply and child care choices in a rationed child care market - Katharina Wrohlich (Institute for the Study of Labor (IZA), 2006)
In this paper, I suggest an empirical framework for the analysis of mothers' labor supply and child care choices, explicitly taking into account access restrictions to subsidized child care. This is particularly important for countries such as Germany, where subsidized child care is rationed and private child care is only available at considerably higher cost. I use a discrete choice panel data model controlling for unobserved heterogeneity to simultaneously estimate labor supply and the demand for child care of German mothers with at least one child under the age of seven years. The model can be used to evaluate different kinds of policy reforms, such as changes in the availability or costs of child care. Results from the illustrating policy simulations show that targeting public expenditures at an extension of child care slots has greater effects on the demand for child care as well as on maternal employment than a reduction of parents' fees to existing slots.
Keywords: J22; J13; C35; 330; child care; labor supply; discrete choice; panel study; Germany; Kinderbetreuung; Arbeitsangebot; Frauen; Familienökonomik; Schätzung; Deutschland